Management of Village Fund Allocation to Improve The Welfare of The People of Torongrejo Village - Maria Stefania Sato; Poppy Indrihastuti; Yayuk Sulistyowati (International Journal of Management and Business, 2025)
This study aims to analyze the management of village fund allocation (ADD) to improve the community's welfare in Torongrejo Village. Using a qualitative method approach, this research deeply explores village fund utilization's planning, implementation, and evaluation process. The study identifies village government strategies to optimize village fund allocation for economic empowerment, infrastructure development, and improving community living standards. Data was collected through in-depth interviews, field observations, and document studies. The research results show that village fund allocation management in Torongrejo Village has significantly contributed to improving community welfare, although some challenges remain in its implementation. The success of managing village fund allocation in Torongrejo is reflected in implementing the principles of good governance. Transparency is shown through information disclosure and community involvement in every program planning and implementation stage. Accountability is built through a strict and systematic accountability mechanism, and supervision involving various elements of society. The village government needs to continue to improve transparency and accountability in managing village funds so that the community can monitor and assess the performance of the village government. Moreover, managing village fund allocation in Torongrejo Village can be more effective in improving community welfare.